Evaluation of the Detonation Characteristics of Aluminized DNAN‐Based Melt‐Cast Explosive by the Detonation Cylinder Test. Issue 4 (9th February 2022) - Yang, Yang; Duan, Zhuoping; Li, Shurui; Zhang, Liansheng; Han, Yong; Huang, Hui; Huang, Fenglei
Abstract: To investigate the detonation characteristics of a new aluminized DNAN‐based melt‐cast explosive RDA‐2 (containing DNAN (2, 4‐dinitroanisole), HMX (cyclotetramethylene tetranitramine) and aluminum), a series of cylinder tests were conducted. The LiF (lithium fluoride) explosive of a similar formulation was also tested to study the influence of aluminum on the detonation characteristics of RDA‐2. The cylinder wall expansion velocities were recorded by Photonic Doppler Velocimetry (PDV). From the experimental data, the detonation velocity, the Gurney energy, the detonation energy, and the CJ pressure of the explosives were calculated. Both the detonation velocity and CJ pressure results indicate that the aluminum seems to have no significant influence on the chemical reaction zone of RDA‐2. The experimental data shows that a large amount of aluminum reacts behind the CJ point. Finally, the parameters of the Jones‐Wilkins‐Lee (JWL) equation of the state of the detonation products were determined. Abstract :